Examine the moderating roles of organization support and government initiative on the intention to adopt cloud computing software as a service among SMEs in Pakistan - Nosheen, Ammber (2025)
Cloud Computing (CC) represents a dynamic information technology paradigm offering on-demand IT resources through a pay-as-you-go framework. Among the array of cloud computing service models, Software as a Service (SaaS) was formulated to deliver IT services efficiently, optimizing computing utilization, power consumption, and performance to reduce costs and augment revenue. Nonetheless, the adoption rates of CC-Saas among Small and Medium Enterprises (SMEs) remain insufficient, and the extent of its diffusion remains inadequately investigated. Additionally, there exists a conspicuous absence of empirical studies focusing on CC-Saas adoption within SMEs in developing countries, specifically in nations like Pakistan. This study examines the moderating role of organization support and Government Initiative to enhance the theoretical model encompassing technological, organizational, and environmental (TOE) factors alongside organizational support (OST) with moderation effects. Moreover, they seek to explore the impact of organisation support and government initiatives on CC-Saas adoption within the SME landscape. Consequently, this study endeavors to investigate the most influential factors through a robust model based on two prominent theories: TOE and OST. Employing a quantitative research approach, 460 questionnaires were distributed randomly among SME managers, professionals, and executives sourced from SMEDA (small and medium enterprise development authority). Of these, 370 questionnaires were returned, with 350 deemed usable for the primary analysis conducted through PLS-SEM. The findings emphasized the statistically significant association between TOE factors and OST with moderation effect and the adoption of CC-Saas. However, government initiatives did not exhibit significance. Notably, organization support from cloud service providers emerged as an influential moderator in CC-Saas adoption, assuming an additional objective role. Furthermore, government initiatives solely in technology readiness demonstrated a significant moderating effect. These findings significantly contribute to the existing knowledge by formulating a CC-Saas adoption for SMEs based on the final model practice of IS and recommendations to policymakers and cloud vendors. This strategy guides policymakers in steering their decisions, especially for the adoption process.